PENGEMBANGAN POTENSI DAYA TARIK WISATA PULAU ATAURO DI DISTRIK DILI, TIMOR-LESTE - Costa Gomes, Miguel Da Costa (Jurnal Master Pariwisata (JUMPA); Volume 01, Nomor 01, Juli 2014DO - 10.24843/JUMPA.2014.v01.i01.p08)
The island of Atauro is a tourist destination located in Dili    District of East Timor.The island has big potential for tourist attractions that deserves to be further developed to be tourist destinations. This study aims to investigate the potential tourist attractions, the internal and external environmental conditions as well as to formulate strategies and programs for sustainable tourism development. This study used IFAS (Internal Factor Analysis System) and EFAS (External Factor Analysis System) are used. This study applies planning theory, tourism area life cycle by Butler, planning and Participation Theory. Data are collected through observation, interviews, and questionnaires.The results showed that there is potential to further develop some tourist attractions in Atauro to be sustainable tourism. Unspoiled natural view, underwater panoramic, extended coral-reef with varieties of fishes, forest with various birds, unique social and cultural life are some of the potential areas for development. The analysis on internal and external environment showed that Atauro is categorized into cell I Grow and Development (the concentration is via vertical integration). The potential for tourism in Atauro Island mainly lays in marine, culture, beaches, history, biking, spring water, seaweed cultivation, cave, spirituality, and sightseeing adventure. The strongest factor of internal environmental condition is the panoramic view, while the weakest factor is the inadequate facilities and infrastructure.